The Role of the Land Deed Maker in the Validity of Land Grant Deeds - Hermawaty, Yenni; Lisiani Prihatinah, Tri; Sulistyandari, Sulistyandari (International Journal Labs, 2024)
As public officials, Land Deed Officials (PPAT, Pejabat Pembuat Akta Tanah) must comply with the rules in the PPAT Position Regulation, including the primary duties, authorities, prohibitions, and PPAT Code of Ethics. This study examines the role of PPAT and the legal consequences of grant deeds canceled by the panel of judges in Supreme Court Decision Number 503K/Ag/2015. This type of research is normative juridical with statutory, conceptual, and case approaches. The data used is secondary data from primary, secondary, and tertiary legal materials. The results show that Muslim Indonesians are subject to the rules in the Compilation of Islamic Law and the Compilation of Sharia Economic Law and use the Religious Courts to resolve disputes. Grant legal acts must be legalized with a Grant Deed, which is the authority of PPAT. In making a Grant Deed, the PPAT must examine the origin of the granted property. The pillars and conditions of grants in KHI and KHES are cumulative and must be fulfilled. The grant can be canceled if one of the elements is not fulfilled. In the case of grant deed Number 112/II/GB/2003, the PPAT needed to fully carry out its role correctly. Despite having carried out duties by several articles in Government Regulation No. 37/1998 jo PP No. 24/2016, the PPAT violated Article 22 and the precautionary principle in the PPAT Code of Ethics. As a result, the grant deed was declared to have no legal force by the Panel of Judges of the Supreme Court. This research shows that violations by PPAT in making grant deeds can cause the deed to be invalid and null and void, eliminating legal certainty for the parties involved. PPAT's adherence to the rules and the precautionary principle is essential to ensure the legal validity of the deed made.